2022
DOI: 10.1021/acs.jpca.2c02525
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Dynamical Characteristics of Hydrogen Bond Bifurcations in Water–Water and Water–Ammonia Dimers: A Path Integral Molecular Dynamics Study

Abstract: We present path integral molecular dynamics results that describe the effects of nuclear quantum fluctuations on equilibrium and dynamical characteristics pertaining to bifurcation pathways in hydrogen bonded dimers combining water and ammonia, at cryogenic temperatures of the order of 20 K. Along these isomerizations, the hydrogen atoms in the molecules acting as hydrogen-bond donors interchange their original dangling/connective characters. Our results reveal that the resulting quantum transition paths compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 84 publications
1
18
0
Order By: Relevance
“…The number of beads was set to P = 128; this number is similar to the ones adopted in several previous studies. 30,33,34,47,48 Forces and energies were computed by implementing an NN fitting algorithm. In the present context, this strategy presents two important advantages: First, it provides estimates with ab initio quality at computer costs much more modest than those obtained from alternative schemes that require onthe-fly electronic structure computations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of beads was set to P = 128; this number is similar to the ones adopted in several previous studies. 30,33,34,47,48 Forces and energies were computed by implementing an NN fitting algorithm. In the present context, this strategy presents two important advantages: First, it provides estimates with ab initio quality at computer costs much more modest than those obtained from alternative schemes that require onthe-fly electronic structure computations.…”
Section: Methodsmentioning
confidence: 99%
“…In order to get satisfactory sampling, each component of each normal mode was coupled to a chain of three Nosé–Hoover thermostats, , with mass parameters set at Q k = k normalB T / ω k 2 , where ω k represents the frequency of the k th normal mode. , Adequate convergence of the different average values typically required harvesting statistics along ∼0.5–1 ns long trajectories. The number of beads was set to P = 128; this number is similar to the ones adopted in several previous studies. ,,,, …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, recent work focused on the implications of nuclear quantum fluctuations on equilibrium and dynamical properties relating to bifurcation routes in hydrogen-bond dimers of water and ammonia. It was shown that the classical over-the-hill approach is substituted with a tunneling-controlled mechanism that, from the perspective of the path integral, can be modeled as coordinated inter-basin migrations of polymer beads [ 73 ]. The application of quantum mechanical approaches was further extended to probe the development of neighboring hydrogen bonds with water molecules.…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%